Cardiac toxicity in cancer survivors. (20th May 2013) - Lenihan, Daniel J.; Oliva, Stefano; Chow, Eric J.; Cardinale, Daniela
Abstract : Cardiac disease is a major concern for cancer survivors, and this can be manifested as cardiac dysfunction from myocardial damage, valvular disease, atherosclerosis, and/or pericardial disease. In this "dialogue" between select European and American investigators, present current perspectives (both similarities and differences) are presented regarding the diagnosis and management of cardiac disease among cancer survivors, with a focus on left ventricular (LV) systolic dysfunction and heart failure. The authors conclude that comprehensive cardiac risk assessment is necessary to optimally manage all cancer survivors, and the integration of common definitions is necessary. Ongoing and future research will need to incorporate cardiovascular management principles in the long‐term assessment of cancer survivors. Cardiac biomarkers, troponin, and the natriuretic peptides are becoming essential in the management of cardiac disease in cancer survivors coupled with periodic use of sophisticated imaging tools. Recognition of specific cancer therapy and the increased cardiovascular risk is an ongoing task that will remain of paramount importance for optimal outcomes among cancer survivors. Cancer 2013;119(11 suppl):2131‐42. © 2013 American Cancer Society . Abstract : Ongoing and future research should incorporate cardiovascular management principles into the long‐term assessment of cancer survivors. Cardiac biomarkers and sophisticated imaging are becoming essential in the management of cardiac disease in cancer survivors; recognizing the increased cardiovascular risk of cancer therapy will remain of paramount importance.